Unexpected Liver Metastasis Three Years after Nephrectomy for Renal Oncocytoma: A Case-report and Review of Literature - Pekka Lammi; Anna Junttila; Essi Ikonen; Arto Salonen; Olli Lahtinen; Antti Kivivuori (Scandinavian Journal of Urology)
N/A